Peculiarities of valence band formation in As-Ge-Se semiconductor glasses - Vakiv, M.; Golovchak, R.; Chalyy, D.; Shpotyuk, M.; Ubizskii, S.; Shpotyuk, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Peculiarities of valence bands formation in As-Ge-Se semiconductor glasses have been investigated within AsxGexSe₁₋₂x cut of glass forming region by highresolution X-ray photoelectron spectroscopy (XPS). It is shown that compositional dependence of XPS valence band spectra of the investigated glasses correlates well with previously obtained data for constituent glasses of binary GexSe₁₋x and AsxGe₁₋x systems. In particular, increase in х leads to the decrease in the intensity of bands at ~2 eV responsible for Se lp-states. The valley at ~3 eV is filled by electronic states originated from Se-GE and Se-As bonds. An accompanying decrease in the intensity of the band at ~5 eV is explained by a decrease in Se 4p bonding states associated with covalent bonds.